The Research on the Spindle Vibration State Suppressor after Remanufacturing - Liu, Ling (Applied Mechanics and Materials, 2014)
The overhung spindle system is studied as the object after remanufacturing, the spindle simplified cantilever and the mathematical model was established based on the simplified equivalent device. The simulation analysis of the dual cantilever was carried out by using ANSYS.The vibration mode and inherent frequency of the cantilever, the deformation caused by the applied loads was given in this paper.It is designed by the linear quadratic optimal control of two state regulator through analyzing the vibration form and loading condition,use of independent modal control algorithm based on the detection of the position feedback control,It is inhibited effectively when a cantilever beam subjected to external transient pulse disturbance caused by two order and higher order system mode vibration,and using the Matlab software programming for active vibration control effects simulation.In addition.Matlab software gave the image result of response of vibration system.Both the brief solution program and the accurate image data which corresponded with vibration theory showed the feasibility and superiority during solving these responses of the spindle vibration system after remanufacturing.Thereby,this research provided an easy and effective method to solve the response of general mechanical vibration system.